2021
DOI: 10.1186/s12983-021-00432-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the coexistence of differentiation and communication in an endemic hare, Lepus yarkandensis (Mammalia, Leporidae) using specific-length amplified fragment sequencing

Abstract: Background The Yarkand hare (Lepus yarkandensis Günther, 1875) is endemic to oasis and desert areas around the Tarim Basin in the Xinjiang Uyghur Autonomous Region of northwest China; however, genome-wide information for this species remains limited. Moreover, the genetic variation, genetic structure, and phylogenetic relationships of Yarkand hare from the plateau mountain regions have not been reported. Thus, we used specific-length amplified fragment sequencing (SLAF-seq) technology to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 95 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…In this study, we used a set of SLAF-seq genome-wide SNP and mtDNA markers to estimate the genetic diversity of Tolai hares in Xinjiang. At the genome-wide level, the genetic diversity of Tolai hares based on SNPs was higher (Table 2) (π = 0.05926, He = 0.37412, Ho = 0.40226, PIC = 0.2974) than that of other reported species, including rabbits (PIC = 0.2-0.2281, He = 0.2511-0.2857, Ho = 0.3072-0.3418, (Ren et al, 2019), and Yarkand hares (π = 0.0655, He = 0.3130, Ho = 0.2852, PIC = 0.2543 (Ababaikeri et al, 2021). The estimated nucleotide diversity of Tolai hares (π = 0.0442) based on mtDNA was also relatively high compared to other Lepus taxa, such as brown hares (π D-LOOP = 0.030, (Minoudi et al, 2018), Yarkand hares (π D-LOOP = 0.033, π CYTB = 0.008, (Shan et al, 2011), and Italian hares (L. corsicanus, π D-LOOP = 0.018, (Pierpaoli et al, Frontiers in Genetics frontiersin.org 2003).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In this study, we used a set of SLAF-seq genome-wide SNP and mtDNA markers to estimate the genetic diversity of Tolai hares in Xinjiang. At the genome-wide level, the genetic diversity of Tolai hares based on SNPs was higher (Table 2) (π = 0.05926, He = 0.37412, Ho = 0.40226, PIC = 0.2974) than that of other reported species, including rabbits (PIC = 0.2-0.2281, He = 0.2511-0.2857, Ho = 0.3072-0.3418, (Ren et al, 2019), and Yarkand hares (π = 0.0655, He = 0.3130, Ho = 0.2852, PIC = 0.2543 (Ababaikeri et al, 2021). The estimated nucleotide diversity of Tolai hares (π = 0.0442) based on mtDNA was also relatively high compared to other Lepus taxa, such as brown hares (π D-LOOP = 0.030, (Minoudi et al, 2018), Yarkand hares (π D-LOOP = 0.033, π CYTB = 0.008, (Shan et al, 2011), and Italian hares (L. corsicanus, π D-LOOP = 0.018, (Pierpaoli et al, Frontiers in Genetics frontiersin.org 2003).…”
Section: Discussionmentioning
confidence: 70%
“…This also occurs in Yarkand hare in Xinjiang. The population genetics of Yarkand hares based on SNPs (Ababaikeri et al, 2021) and mtDNA (Shan et al, 2011) showed a systematic geographical distribution pattern and genetic differentiation between the north and southwest populations, which may have been caused by geographical isolation and different living environment. It is concluded that geographical isolation and complex habitats can affect hare populations' genetic structure and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with Oryctolagus cuniculus and other hares, L. yarkandensis has many specific adaptations to arid environments. These adaptations have been explored using SNP analysis, population structure (Ababaikeri et al, 2021), mitochondrial genome sequencing, phylogenetic tree construction (Shan et al, 2021), as well as aquaporin (AQP) expression in the kidney, gastrointestinal tract, and lungs (Zhang et al, 2019a;Zhang et al, 2019b;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%